Design and Simulation of a Low-Actuation-Voltage MEMS Switch - Mafinejad, Yasser; Kouzani, Abbas; Matekovits, Ladislau (EAI Endorsed Transactions on Energy Web, 2015)
This paper presents a low-actuation-voltage micro-electro-mechanical system (MEMS) capacitive shunt switch which has a very large bandwidth (4 GHz to 24 GHz). In this work, the isolation of MEMS switch is improved by adding two short high impedance transmission lines at the beginning and end of a coplanar waveguide (CPW). Simulating the switch demonstrates that a return loss (S11) is less than -26 dB for the entire frequency band, and perfect matching at 20 GHz in upstate position. A ramp dual pulse driver is also designed for reducing the capacitive charge injection for considering the reliability of the switch. The simulation results show that the shifting of voltage due to the capacitive charge is reduced by more than 35% of the initial value. Finally, the dynamic behavior of the MEMS switch is simulated by modal analysis and using CoventorWare to calculate the natural frequencies of the switch and its mode shapes. The switching ON and OFF time are 4.48 and 2.43 µs, respectively, with an actuation voltage of less than 15 V.